Is Congenital Syphilis Really Congenital Syphilis? - Yi Li; Bernard Gonik (Hindawi Limited, 2006)
Detroit has recently been distinguished as having the highest congenital syphilis rate in the United States (250.3 cases per 100 000 live births in Detroit versus 10.3 in the US). However, depending on each health department's followup and CDC reporting, these data may not accurately reflect the true congenital syphilis rate. This study examines the reported cases over a three-year time period with focus on the criteria used for diagnosis. All local health department congenital syphilis CDC collection forms (form 73.126) were reviewed for the years in question. The reported congenital syphilis cases in the year 2002-2004 in Detroit were reviewed. No cases met confirmed case criteria and few probable cases were based on neonatal evaluations. The majority of "congenital syphilis" cases were established based on incomplete maternal data such as missing followup serologic titers in the absence of complete neonatal information. In conclusion, although the reported congenital syphilis rate in Detroit is alarmingly high, the true occurrence of congenital syphilis is likely to have been overstated. A health department reporting program that includes more diligent neonatal followup would allow for a more accurate representation of this public health concern.